The Project Based Learning Integrated Ethnoscience: A Model of Learning to Enhance Scientific Literacy Among Pre-Service Elementary Teacher - Muhamad Chamdani; Kartika Chrysti Suryandari; Murwani Dewi Wijayanti (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to determine the effect of ethnoscience-based Project-Based Learning (PjBL) on students' science literacy, measure the level of improvement in students' science literacy, and analyze students' science literacy levels in terms of context, competence, and knowledge aspects. The research uses a mixed-method approach with a sequential explanatory design. The quantitative part of the study is conducted using a quasi-experiment, while the qualitative part employs field research. Data analysis techniques include the Mann-Whitney U test for quantitative data and triangulation techniques to validate data. The Miles and Huberman and Saldana model is used for qualitative data analysis.The study found that the use of ethnoscience-based PjBL significantly affects students' science literacy, with a significance value of 0.003 < 0.05. The increase in science literacy in the experimental class is categorized as high, at 0.71, while the control class shows a moderate category, at 0.60. In terms of science literacy levels, the experimental class reached a minimum of level 4, while the control class still had students at level 3. This means that students in the experimental class had better science literacy compared to the control class, particularly in terms of prospective elementary school teachers. Among the three aspects of science literacy, the competence aspect was the highest in both the experimental and control classes compared to the other aspects.